6th Dubrovnik conference on sustainable development of energy water and environment systems - Todorović, Jovan (Journal of Applied Engineering Science, 2011)
The Conference on Sustainable Development of Energy,Water and Environment Systems (SDEWES), was held forits 6th consecutive time, on September 25 - 29, 2011 in Dubrovnikin Croatia.
Keywords: sustainable use; Sustainable development; energy use; Dubrovnik